La decisión absoluta en el pensamiento kierkegaardiano - Binetti, María (Pontificia Universidad Católica del Perú. Fondo Editorial, 2004)
El artículo se propone mostrar la originalidad de la libertad kierkegaardiana, concentrada en una decisión absoluta que determina por entero la realidad del sujeto singular existente. La decisión produce la síntesis de la existencia personal, unificando todos los elementos y dimensiones que configuran la vida humana, y armonizando las fuerzas del yo hacia la confluencia en un mismo fin, a saber, en el Ser absoluto. La unidad interior producida por la decisión es posible gracias al "salto" trascendente de la libertad, por el cual la existencia humana se afirma en el fundamento uno y simple del cual ella procede.

“Absolute Decision in Kierkegaard’s Thought”. This paper attempts to show the originality of Kierkegaard’s notion of freedom, that brings into focus an absolute decision that wholly determines the reality of the singular existing subject. Such decision brings forth the synthesis of personal existence, unifying all the elements and dimensions that constitute human life, and harmonizing the strengths of the self toward their confluence in one final end, which is absolute Being. Immanent unity brought about by the decisión is possible due to a transcendental “leap” of freedom, whereby human existence affirms itself on the One and Simple Foundation out of which it procedes.
Keywords: Filosofía; https://purl.org/pe-repo/ocde/ford#6.03.01